First record of Eualus drachi Noël, 1978 (Decapoda: Caridea) in the Adriatic Sea - Kirinčić, Marin (Array, 2021)
Three specimens of decapod shrimp Eualus drachi Noël, 1978, were found in the red coral rem-nant collected for commercial purposes near the island Sveti Andrija, Croatia. It is the first record of this species in the Adriatic Sea. The decapod biodiversity of deeper coralligenous habitats, such as the red coral colonies, is poorly investigated in contrast to coastal areas and soft bottoms of traditional trawling grounds. This paper highlights the usefulness of examining the remnants of a commercial coral extraction originating from previously less investigated marine habitats in order to improve the knowledge on the biodiversity of such habitats.